2011
DOI: 10.1002/j.2334-5837.2011.tb01222.x
|View full text |Cite
|
Sign up to set email alerts
|

4.6.3 An MBSE Feasibility Study using the Systems Integration Sandpit

Abstract: Model-Based Systems Engineering (MBSE) involves a focal shift from document-centric to model-centric systems engineering practices in which the model becomes the primary systems engineering artifact to represent the system specification and design. For an organization, early adoption of new approaches such as MBSE requires careful consideration of the cultural change, staff training needs, and introduction mechanisms to inform the cost-benefit tradeoff and to ascertain the level of risks. To this end, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…18,33 Stakeholder involvement All stakeholders should be involved throughout the duration of the project, 15,28,31,34,39 but do not need to be exposed to the model in greater detail than necessary. 39,53 It can also be a challenge to "align all stakeholders with the selected modeling objectives and methodology." 43 Tools MBSE tools are reported to have a significant learning curve.…”
Section: Necessity Of Mbse Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,33 Stakeholder involvement All stakeholders should be involved throughout the duration of the project, 15,28,31,34,39 but do not need to be exposed to the model in greater detail than necessary. 39,53 It can also be a challenge to "align all stakeholders with the selected modeling objectives and methodology." 43 Tools MBSE tools are reported to have a significant learning curve.…”
Section: Necessity Of Mbse Methodsmentioning
confidence: 99%
“…1,32 How data will be stored, accessed, and exchanged should be thought out as well. 28,53 Leadership/management support "creates a strong MBSE infrastructure." 6,57 Integration Integration is necessary in order to provide end-to-end traceability throughout a system that is housed over multiple tools/models/networks.…”
Section: Lessons Learned Categories Literature Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation indicates that there is a very strong case for the use of MBSE in defence capability projects and that the benefits extend well beyond the production of models to support the required project documentation. Secondly, a subsequent study in 2010 (Do et al, 2011), was conducted to investigate efficiency and efficacy of MBSE tools and methodology via a case study approach. One of the case studies was the Land 19, Phase 7 defence project (Ground-Based Air and Missile Defence system), and is described herein.…”
Section: Case Study -Ground-based Air Missile Defence Systemmentioning
confidence: 99%
“…Recent research identified that the languages and tools employed in current MBSE practices (such as SysML and the CORE TM representations) represent requirements as text strings and as such offer none of the proven capabilities of Cook and Scott's prototypes such as syntactically correct requirements entry and evaluation of the requirements set for correctness, feasibility, consistency, duplication and coherency (Do et al, 2011). This research challenge will address how to extend the latest generation MBSE tools, which will be provided by the tool vendor partner, to include the sort of enhanced functionality already demonstrated by members of the team.…”
Section: Research Challenges and Future Developmentmentioning
confidence: 99%